Distribution and seasonal variations of n-alkanes in some species of molluscs from Shatt Al-Arab river - Al-Saad, A.A.; Farid, W.A.; Al-Adhub, A.Y. (Mesopotamian Journal of Marine Sciences, 2022)
The seasonal variations of n-alkanes compounds in molluscs of Shatt Al-Arab river have been studied. The species of molluscs were the snails, Lymnaea auricularia, Theodoxus jordani, Physa acuta, Melanopsis nodosa, Melanoides tuberculata while the bivalves were Corbicula fluminea and Corbicula fluminalis. The molluscs were collected from different locations of Shatt Al-Arab river (along the region extended from Abu-Al-Khasib to Garmat-Ali) during 2004 and 2005. Each species consisted of at least 350 adults of uniform size of individuals. The n-alkanes compounds from species of molluscs were extracted and analyzed by high resolution capillary gas chromatography. The total concentrations of n–alkanes in the molluscs varied from 1.50 μg/g dry weight in the T. jordani to 8.78 μg/g dry weight in the C. fluminea during summer and from 2.26 μg/g dry weight to 12.37 μg/g dry weight during autumn. While ranged from 3.15 μg/g dry weight to 12.44 μg/g dry weight and from 1.78 μg/g dry weight to 5.31 μg/g dry weight during winter and spring. The study confirmed lower concentrations of n-alkanes compounds in the molluscs of Shatt Al-Arab river during summer and spring while higher concentrations were recorded during winter and autumn. This is due to several factors which could act to produce such seasonal variations.